Qandeel-e-adab 3 qawaid e insha - Maaqsod,Saeed (Lahore: Asian education publisher, 2024)
Qandeel-e-Adab 3" is a part of a series of Urdu literature textbooks used in Pakistan. It covers various literary genres like poetry, prose, essays, and stories that reflect cultural, moral, and ethical teachings.
Keywords: Qandeel e adab- textbook